Ionic liquid and deep eutectic solvent-enabled food freshness sensing: From molecular interactions to integrated intelligent monitoring systems - Xinhui Zhou; Yuan Huang; Yuping Liu; Zhangyan Sun; Yuxiao Hu; Mingfeng Xu; Xueqin Yang; Rongrong Yu (Trends in Food Science & Technology, 2026)

Semaglutide treatment reverses HFD induced hippocampal microglia activation and improves cognitive dysfunction - Haodong Gong; Junlu Liu; Yihan Wang; Xufan Lin; Guangsen Wu; Yichao Ou; Mingfeng Zhou; le Yang; Junxiang Peng; Xinyun Ye; Yongjia Wang; Fei Xu; et al. (Tissue and Cell, 2026)

Pickering emulsions stabilized by bovine bone gelatin - xanthan gum conjugates: an effective carrier for curcumin encapsulation - Mingfeng Sun; Wenxia Wu; Huanhuan Yang; Mou Zhao; Xiang Zhou; Nengmao Chen; Jingtao Sun; Shiling Lu; Qingling Wang; Juan Dong (Food and Bioproducts Processing, 2026)

Tree-inspired solar interfacial evaporation: From isolated structural mimicry to integrated functional synergy - Zhicheng Xu; Xintao Zhou; Zhongqiu Luo; Mingfeng Zhong; Zhijie Zhang (Journal of Environmental Chemical Engineering, 2026)

Progress on the addition of exogenous lipids to surimi: A review - Li Yuan; Mingfeng Xu; Abdul Razak Monto; Wengang Jin; Nannan Zhou; Zhiyu Xiong; Tong Shi; Ruichang Gao (Food Chemistry, 2026)

Adaptive graph learning with dynamic neural ODE for feeding intensity analysis of pearl gentian grouper in a recirculating aquaculture system - Hongpo Wang; Zeshuang Ma; Hong Zhou; Yunchen Tian; Haohui Liu; Zhanshuo Sun; Lei Jia; Jincheng Hu; Mingfeng Hu (Aquacultural Engineering, 2026)

Enhancement of macadamia protein solubility and functionality using combined pH-shift-heat treatment: Role of ionic environment (PBS vs water) - Xixiang Shuai; Mingfeng Fang; David Julian McClements; Tingting Chen; Zhipan Wang; Liqing Du; Ming Zhang; Wei Zhou; Taotao Dai; Jihua Li; Jun Chen (Food Chemistry, 2026)

Intercropping enhances soil organic carbon accumulation by modulating microbial interactions in saline-alkali soils - Lijun Zhang; Guixiang Zhou; Jiabao Zhang; Lin Chen; Congzhi Zhang; Donghao Ma; Hui Zhang; Jian Feng; Mingfeng Liu (Applied Soil Ecology, 2026)

Succession patterns, environmental connections, and assembly mechanisms of gut microbiota in the giant freshwater prawn (Macrobrachium rosenbergii) across lifespan - Songbao Zou; Yao Zheng; Julin Yuan; Meng Ni; Mei Liu; Dan Zhou; Qiang Gao; Mingfeng Deng; Ruichen Wang; Xin Zhang (Aquaculture, 2026)

A DFN–DEM approach to determine equivalent mechanical parameters of rock mass with different joint densities - Liang Wang; Shijie Zhou; Juan Huang; Mingfeng Lei; Yonggang Han; Jian Zhang; Chaojun Jia (Bulletin of Engineering Geology and the Environment, 2026)

Metabolic profiling of triptophenolide in rat plasma, urine, bile and faeces after intragastric administration - Mingfeng Jiang; Qiang Hou; Shuilian Wu; Xiaofan He; Tingting Zhang; Rongjing Zhou (Natural Product Research, 2025)

Isolation and structural elucidation of two novel lignans from the flowers of Gardenia jasminoides with potent α-glucosidase inhibitory activity - Qingsen Shao; Huiyu Li; Mingfeng Li; Wei Yi; Qiugui Zhou; Lijuan Zheng; Meng Wang; Hong-mei Hu; Chao Wen; Yun Tang; Wei Li (Phytochemistry Letters, 2025)

Changes of soil nitrate accumulation and the abundance and structure of nitrogen cycling microbial communities during long-term solar greenhouse vegetable cultivation - Mingxia Yang; Ningning Zhou; Mingfeng Li; Zhujun Chen; Jianbin Zhou; Xiaofang Deng (Journal of Soils and Sediments, 2025)

Temperature effects on the micro-to-macro mechanical and creep properties of impurity salt rock - Chengxing Zhao; Cheng Lyu; Mingfeng Yang; Yunhui Zhang; Ping Zhou (Bulletin of Engineering Geology and the Environment, 2025)

Nitrogen Doping Engineering of V2CTx based Zinc Ion Hybrid Microcapacitors with Quadruple High Energy Density - Wei Lai; Sairao Zhao; Mengdi Guo; Di Wu; Shijun Luo; Chuankun Zhang; Tao Huang; Wenbin He; Mingfeng Li; Xin Zhou; Xiao Luo; Jian Li; et al. (Chemical Engineering Journal, 2024)

Dynamic response of a transmission conductor following delayed ice shedding by reduced-scale model test - Yuelong Zhang; Yong Guo; Wenjuan Lou; Weizheng Zhou; Mingfeng Huang (Cold Regions Science and Technology, 2024)

Influence of climate and land use on watershed anthropogenic phosphorus inputs and riverine phosphorus export dynamics: A global analysis - Hao Wu; Xinyi Jiao; Yucang Wang; Mingfeng Wang; Jia Zhou; Kaibin Wu; Dingjiang Chen (Science of The Total Environment, 2024)

Comparative analysis of the effect of nano‑copper and Cu2O treatment on Cryptocaryon irritans tomonts in large yellow croaker (Larimichthys crocea) farming - Ying Zhou; Quanyin Liu; Kun Hu; Mingfeng Ge; Shengwei Xu; Chengyi Huang; Shan Jin; Rongrong Ma; Jianping Wang (Aquaculture, 2023)

Evaluation of three prevalent global riverine nutrient transport models - Xinyi Jiao; Jia Zhou; Minpeng Hu; Mingfeng Wang; Hao Wu; Kaibin Wu; Dingjiang Chen (Environmental Science and Pollution Research, 2023)

Numerical Simulation Study on Ship–Ship Interference in Formation Navigation in Full-Scale Brash Ice Channels - Chang Xie; Li Zhou; Mingfeng Lu; Shifeng Ding; Xu Zhou (Journal of Marine Science and Engineering, 2023)
Formation navigation in brash ice channels is increasingly utilized by merchant vessels in the Arctic and Baltic Sea, offering benefits such as improved efficiency and reduced carbon emissions. However, ship–ship interference poses a significant challenge to this method, impacting resistance performance. This paper presents full-scale simulations using the CFD–DEM coupling method in brash ice channels, which is validated by comparing simulation results with ice tank measurements. By varying the distance between two ships from 0.05 to 5 ship lengths, ship–ship interference in full-scale brash ice channels is analyzed using the CFD–DEM coupling strategy. The study examines hydrodynamic and ship–ice interactions, ice resistance effects, and simulation results. It is found that ship-to-ship distance significantly influences the velocity field, dynamic pressure distribution on the hull, and hydrodynamic interaction forces. Distances less than one ship length result in increased water resistance for the forward ship and decreased resistance for the rear ship. The forward ship demonstrates favorable interference with the ice accumulation of the rear ship. When distances are less than two ship lengths, the ice resistance of the forward ship remains mostly unaffected, while the ice resistance of the rear ship decreases as the distance decreases. These insights enhance our understanding of ship–ship interference in formation navigation, aiding in the optimization of brash ice channel navigation strategies.

Soil nitrification process played a key role in alleviating continuous cropping limitation induced by fumigation - Jing Xiong; Yongjun Liu; Tianbo Liu; Shuguang Peng; Mingfeng Cao; Zhenhua Wang; Lei Zhou; Junliang Zou; Zhenghua Liu; Jixiang Ai; Yabing Gu; Huaqun Yin; et al. (Plant and Soil, 2023)

Nitrogen Application Promotes Drought-Stressed Sugar Beet Growth by Improving Photosynthesis, Osmoregulation, and Antioxidant Defense - Hongliang Zhou; Pengjie Xu; Lijuan Zhang; Ruimin Huang; Mingfeng Yang; Kaiyong Wang; Hua Fan (Journal of Soil Science and Plant Nutrition, 2023)

Strength and structural variations in dredger fill subjected to vacuum dynamic consolidation - You Zhou; Hongtao Fu; Tian Jin; Mingfeng Li; Junfeng Ni (Marine Georesources & Geotechnology, 2022)

Identification of Prognostic Signatures of Alternative Splicing in Glioma - Yu Zeng; Peidong Zhang; Xizhao Wang; Ke Wang; Mingfeng Zhou; Hao Long; Jie Lin; Zhiyong Wu; Liang Gao; Ye Song (Journal of Molecular Neuroscience, 2020)

First report of summer canker caused by Pectobacterium carotovorum subsp. actinidiae on kiwifruit in Jiangxi, eastern China - MingFeng Yan; Bing Liu; ManFei Zou; Ying Zhou; JunXi Jiang (Journal of Plant Pathology, 2019)

Differentiation of Schisandra chinensis and Schisandra sphenanthera using metabolite profiles based on UPLC-MS and GC-MS - Zhiyong Guo; Aihua Zhao; Tianlu Chen; Guoxiang Xie; Mingmei Zhou; Mingfeng Qiu; Wei Jia (Natural Product Research, 2012)